The impact of economic diversification on improving the investment climate in Iraq for the period 2003-2014 - Fahd, Aysar Yaseen; Jasm, Ahmed Muhammad (Journal of University of Human Development, 2017)
This study aims to analyze the nature and volume of FDI inflows to Iraq during the period between 2003 and 2014 with reference to its importance in diversifying sources of income and reduce the risk of over-reliance on oil revenues, which exceed 97% of total public revenues. The study showed that the lack of pre-drawn strategy and prevented in attracting domestic and foreign investment without making the Iraqi economy a favorable climate to attract investment or directing those investment which entered to the sectors that are capable to contribute to the achievement of a genuine development through their effective contribution to capital formation and to its connections with the front and rear rest sectors.